The ACTA and the plurilateral enforcement agenda : genesis and aftermath - Roffe, Pedro; Seuba, Xavier, 1977- (Cambridge University Press, 2014)
"The Anti-Counterfeiting Trade Agreement (ACTA) is the most important effort undertaken to lay down a plurilateral legal framework for the enforcement of intellectual property rights. With the view to learn more about the origins of this treaty, the process leading to its conclusion and its implications for law making in this field, The ACTA and the Plurilateral Enforcement Agenda: Genesis and Aftermath analyses in great depth both the context and the content of the agreements. In order to attain this objective, a large and diverse group of experts - renowned scholars, policy makers and civil society actors - who represent different perspectives on the necessary balance between intellectual property enforcement and other economic and social interests have been gathered together. This book is the most comprehensive analysis of ACTA, and of its relation with ongoing initiatives to improve enforcement of intellectual property and norms pertaining to a range of international legal regimes, conducted so far"--